Salinity tolerance, hyposaline stress recovery, and survival of the nemertean worm, Carcinonemertes carcinophila (Nemertea) in relation to its host, the Atlantic blue crab, Callinectes sapidus - Alexandria K. Pomroy; Alexandra K. Schneider; Jeffrey D. Shields (PLoS ONE, 2025)
Carcinonemertes carcinophila is a nemertean worm from a family of marine symbionts specialized in eating the eggs of decapod crustaceans. This species infests the Atlantic blue crab, Callinectes sapidus, a native to the Western Atlantic and Gulf of Mexico waters. Its host, the mature female blue crab, is euryhaline, migrating from low to high salinity waters during its adult life, rather than being exclusively marine. Unlike C. carcinophila, most species of marine nemerteans are stenohaline, living exclusively in high salinity waters. The salinity tolerance of C. carcinophila has not been well examined. This study used field-collected frequency data to assess the infestation intensity of nemerteans in relation to salinity regimes, and microcosm experiments to investigate the salinity tolerance and survival of C. carcinophila under hyposaline stress. These investigations also provide information on the nemertean’s life history in relation to the spawning migration of female blue crabs. A multi-stage General Linear Model was used to test our hypothesized positive relationship between salinity and the probability of nemertean abundance on mature female crabs. Experiments confirmed that salinities of 20–30 psu were ideal for the survival of C. carcinophila and revealed the distinct ability of this species to acclimate rapidly to mesohaline conditions as low as 10 psu. This species was also able to withstand oligohaline stress (5 psu) for up to 39 hours. The wide range in salinity tolerance (10–30 psu) indicates that C. carcinophila has evolved to survive in similar euryhaline environments as its host. In addition to the wide salinity tolerance of the worm, the ability to withstand hyposaline stress indicates that rapid salinity changes in the blue crab’s natural environment does not limit the reliability of C. carcinophila as a biomarker for the spawning history of blue crabs.